2017
DOI: 10.5312/wjo.v8.i3.221
|View full text |Cite
|
Sign up to set email alerts
|

Development of an internally braced prosthesis for total talus replacement

Abstract: Total loss of talus due to trauma or avascular necrosis, for example, still remains to be a major challenge in foot and ankle surgery with severely limited treatment options. Implantation of a custom made total talar prosthesis has shown promising results so far. Most important factors for long time success are degree of congruence of articular surfaces and ligamentous stability of the ankle. Therefore, our aim was to develop an optimized custom made prosthesis for total talus replacement providing a high leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 28 publications
(41 reference statements)
0
26
0
1
Order By: Relevance
“…10,11 Other authors have shown that total talus replacements can also be used as salvage for total ankles that have significant talar subsidence. [13][14][15] Recently, authors from our institution have shown good radiographic outcomes following third-generation custom 3D printed total talus replacement for talar AVN 8 ; however, there have not been clinical outcomes reported outside of scattered case reports, with the largest series being only 2 patients. 10…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Other authors have shown that total talus replacements can also be used as salvage for total ankles that have significant talar subsidence. [13][14][15] Recently, authors from our institution have shown good radiographic outcomes following third-generation custom 3D printed total talus replacement for talar AVN 8 ; however, there have not been clinical outcomes reported outside of scattered case reports, with the largest series being only 2 patients. 10…”
Section: Introductionmentioning
confidence: 99%
“…It has been speculated that proper fit is of utmost importance in TTR, correlating with longevity. 11,14,18 In the 36-year follow-up study by Harnroongroj and Harnroongroj, 11 2 patients failed acutely because of size mismatch. Ando et al 14 described a risk for anterior instability because the deltoid and anterior talofibular ligaments are divided during the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…The restoration of talar alignment and anatomy, synthetically, could be beneficial in these patients, and early case reports have begun to yield satisfactory results. [16][17][18] Larger case series are needed to appropriate this modality rather than salvage arthrodesis. At the conclusion of this study, there have not been any complications to report.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…X-rays have also been used to measure the cardiopulmonary resuscitation (CPR) force and to look at replacement joint force, and the internal prosthetic forces that can be withstood [ 7 - 8 ].…”
Section: Reviewmentioning
confidence: 99%